Design of a high performance thin all-solid-state supercapacitor mimicking the active interface of its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2013)
Here we report an all-solid-state supercapacitor (ASSP) which closely mimics the electrode-electrolyte interface of its liquid-state counterpart by impregnating polyaniline (PANO-coated carbon paper with polyvinyl alcohol-H2SO4 (PVA-H2SO4) gel/plasticized polymer electrolyte. The well penetrated PVA-H2SO4 network along the porous carbon matrix essentially enhanced the electrode-electrolyte interface of the resulting device with a very low equivalent series resistance (ESR) of 1 Omega/cm(2) and established an interfacial structure very similar to a liquid electrolyte. The designed interface of the device was confirmed by cross-sectional elemental mapping and scanning electron microscopy (SEM) images. The PANI in the device displayed a specific capacitance of 647 F/g with an areal capacitance of 1 F/cm(2) at 0.5 A/g and a capacitance retention of 62% at 20 A/g. The above values are the highest among those reported for any solid-state-supercapacitor. The whole device, including the electrolyte, shows a capacitance of 12 F/g with a significantly low leakage current of 16 mu A(2). Apart from this, the device showed excellent stability for 10000 cycles with a coulombic efficiency of 100%. Energy density of the PANI in the device is 14.3 Wh/kg.
Keywords: all-solid-state; cyclic voltametry; impedance analysis; polyaniline; polyvinyl alcohol; supercapacitor

3D polyaniline porous layer anchored pillared graphene sheets: enhanced interface joined with high conductivity for better charge storage applications - Sekar, Pandiaraj; Anothumakkool, Bihag; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
Here, we report synthesis of a 3-dimensional (3D) porous polyaniline (PANI) anchored on pillared graphene (G-PANI-PA) as an efficient charge storage material for supercapacitor applications. Benzoic acid (BA) anchored graphene, having spatially separated graphene layers (G-Bz-COOH), was used as a structure controlling support whereas 3D PANI growth has been achieved by a simple chemical oxidation of aniline in the presence of phytic acid (PA). The BA groups on G-Bz-COOH play a critical role in preventing the restacking of graphene to achieve a high surface area of 472 m(2)/g compared to reduced graphene oxide (RGO, 290 m(2)/g). The carboxylic acid (-COOH) group controls the rate of polymerization to achieve a compact polymer structure with micropores whereas the chelating nature of PA plays a crucial role to achieve the 3D growth pattern of PANI. This type of controlled interplay helps G-PANI-PA to achieve a high conductivity of 3.74 S/cm all the while maintaining a high surface area of 330 m(2)/g compared to PANI-PA (0.4 S/cm and 60 m(2)/g). G-PANI-PA thus conceives the characteristics required for facile charge mobility during fast charge-discharge cycles, which results in a high specific capacitance of 652 F/g for the composite. Owing to the high surface area along with high conductivity, G-PANI-PA displays a stable specific capacitance of 547 F/g even with a high mass loading of 3 mg/cm(2), an enhanced areal capacitance of 1.52 F/cm(2), and a volumetric capacitance of 122 F/cm(3). The reduced charge-transfer resistance (RCT) of 0.67 O displayed by G-PANI-PA compared to pure PANI (0.79 O) stands out as valid evidence of the improved charge mobility achieved by the system by growing the 3D PANI layer along the spatially separated layers of the graphene sheets. The low RCT helps the system to display capacitance retention as high as 65% even under a high current dragging condition of 10 A/g. High charge/discharge rates and good cycling stability are the other highlights of the supercapacitor system derived from this composite material.
Keywords: durability; ionic accessibility; phytic acid; pillaring; polyaniline; restacking